Assessment of insertion/deletion polymorphism of the angiotensin-converting enzyme gene in abdominal aortic aneurysm and inguinal hernia. (February 2013) - Antoniou, George A; Lazarides, Miltos K; Patera, Stefania; Antoniou, Stavros A; Giannoukas, Athanasios D; Georgiadis, George S; Veletza, Stavroula Vouliana
The aim of the paper is to determine whether the angiotensin-converting enzyme (ACE) gene insertion/deletion (I/D) polymorphism is associated with abdominal aortic aneurysm (AAA) and inguinal hernia. A case-control study was conducted in 264 subjects: 65 patients with AAA, 91 patients with inguinal hernia, 19 patients with both AAA and hernia, and 89 controls were investigated for the ACE I/D polymorphism. Genotype analysis was performed using a polymerase chain reaction technique. Significant differences in the genotype between the patient groups and controls were identified (aneurysm versus control, P = 0.011; aneurysm plus hernia versus control, P = 0.022; hernia versus control, P = 0.001), whereas no differences were found within patient groups. Patients with AAA and/ or hernia had an increased prevalence of I/D heterozygosity, which persisted even after adjusting for differences in confounding clinical variables (aneurysm versus control, OR 0.3, 95% CI 0.2–0.8, P = 0.005; aneurysm plus hernia versus control, OR 0.3, 95% CI 0.1-0.9, P = 0.040; hernia versus control, OR 0.4, 95% CI 0.2–0.7, P = 0.004). In conclusion, an association between the heterozygote ACE I/D state and the presence of AAA and/or hernia was identified. The role of the ACE I/D polymorphism in aneurysm and hernia needs further investigation.